Association between Fluoride Toxicity, Oxidative Stress, and Pregnancy Complications in Women Living in Fluorosis Areas - Lalla Asmaa Katir Masnaoui; Habiba Bouchab; Abdellatif Rahim; Riad El Kebbaj; Abdelkhalid Essamadi (مجلة بغداد للعلوم)
The purpose of this study was to investigate the relationship between high plasma fluoride levels, oxidative stress, and pregnancy complications (abortion, intrauterine fetal death, preterm birth, and preeclampsia) in women living in Settat province, Morocco. Blood samples were collected from pregnant women with normal gestation (n=60), abortion (n=20), intrauterine fetal death (n=10), premature delivery (n=20), and preeclampsia (n=20). Afterwards, plasma fluoride levels and erythrocyte enzymatic activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx) were determined. The results revealed that plasma fluoride levels were significantly lower in women who had normal pregnancies, with a concentration of 0.030±0.003 mg/l, compared to those presenting with abortion, intrauterine fetal death, preterm birth, and preeclampsia, with concentrations of 0.040±0.002, 0.037±0.002, 0.034±0.004 and 0.034±0.003 mg/l, respectively. In addition, SOD activity was significantly increased in women with pregnancy complications, whereas CAT and GPx activities were decreased compared to women with normal pregnancies. Moreover, there was a strong correlation between plasma fluoride levels, antioxidant activities, and pregnancy complications. The presence of high plasma fluoride levels could lead to an increase in the prevalence of abortion, intrauterine fetal death, preterm birth, and preeclampsia, via the oxidative stress pathway in pregnant women living in Settat province, Morocco.